SISTEM PENDUKUNG KEPUTUSAN PENJURUSAN SISWA MENGGUNAKAN ALGORITMA SIMPLE ADDITIVE WEIGHTING - Sutrisno Sutrisno; Yustina Retno Wahyu Utami; Andriani Kusumaningrum, (Jurnal Ilmiah SINUS, 2018)
Inappropriately high school majors can be detrimental to students in the future. With the right majors are expected to maximize the potential, talent and ability of individual students, so that will maximize the academic value of these students. The method of majors conducted in a school is basically still using conventional methods so there are some weaknesses of the method and in the determination of its course only based on ranking, without specifying the weight of each criteria, with the method based on the analysis and experience that happened there are still some students can not compete with his classmates in developing his academic potential and ultimately to solve the problem in one school to re-clarify at the beginning of the even semester which aims to map the ability of each student and the necessity to build a student majors application based on the academic potential that is able to generate maximum decisions from each student, by looking at the existing problems it is needed an alternative solution that is by designing and building Supporting System Decision in Simple Additive Weighting (SAW) method, supported by Unified Modeling Language (UML) as application design, PHP as programming language and MySQL as its database. In the test of the built application, using the Blackbox method, and the system feasibility test results using 25 test attributes, 21 valid attributes and 4 invalid attributes and a feasibility value generated from the system of 84%, thus the application is eligible to use despite the repair and development still needs to be improved.